Effects of Tumor-Derived Exosome Programmed Death Ligand 1 on Tumor Immunity and Clinical Applications - Shao, Bo; Dang, Qin; Chen, Zhuang; Chen, Chen; Zhou, Quanbo; Qiao, Bingbing; Liu, Jinbo; Hu, Shengyun; Wang, Guixian; Yuan, Weitang; Sun, Zhenqiang (Frontiers in Cell and Developmental Biology, 2021)
Programmed death ligand 1 (PD-L1) is a typical immune surface protein that binds to programmed cell death 1 (PD-1) on T cells through its extracellular domain. Subsequently, T cell activity is inhibited and tumor immune tolerance is enhanced. Studies have shown that PD-L1 is not only expressed on the cell surface but also released from tumor cells. In particular, exosomal PD-L1 plays an unfavorable role in tumor immunosuppression. This review aims to summarize the available evidence regarding the biological characteristics of exosomal PD-L1 in tumor immunity, with a particular focus on the mechanisms in different cancers and clinical prospects.